If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 + -5a = -1(-2 + 4a) + -8 -6 + -5a = (-2 * -1 + 4a * -1) + -8 -6 + -5a = (2 + -4a) + -8 Reorder the terms: -6 + -5a = 2 + -8 + -4a Combine like terms: 2 + -8 = -6 -6 + -5a = -6 + -4a Add '6' to each side of the equation. -6 + 6 + -5a = -6 + 6 + -4a Combine like terms: -6 + 6 = 0 0 + -5a = -6 + 6 + -4a -5a = -6 + 6 + -4a Combine like terms: -6 + 6 = 0 -5a = 0 + -4a -5a = -4a Solving -5a = -4a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '4a' to each side of the equation. -5a + 4a = -4a + 4a Combine like terms: -5a + 4a = -1a -1a = -4a + 4a Combine like terms: -4a + 4a = 0 -1a = 0 Divide each side by '-1'. a = 0 Simplifying a = 0
| -15=x/2-3 | | 2/5-5 | | N+7=9+18 | | (X+8)=(2x-3) | | 8-3x=5x^6 | | 2/3n-5n | | -42+15= | | X^4-6x^2+8= | | 6=4(h+3)-2 | | c=10x+1200 | | 22.6=6x-2 | | .5-.02x=.1 | | k=-3+8+(-9) | | X^5-6x^3+8x= | | 5y=10+10x | | 9log(x-3)+5=18 | | -4+(-5)+6=m | | 6e^3x=84 | | .4(x-5)=.2(10-12x)+x | | 20z(2/z-1/5z) | | 3y=10+10x | | 7x-13=190 | | 9v=24+6v | | 6+5(-4)=t | | S=48+(-2s) | | 6y+2(y-2)=5(y+1)-2 | | (x*x)+(4x)-32=0 | | 3(8bx+y)=23bx-4y | | 25a=81*100 | | -2+x+10=4x+23 | | f=-52+52 | | 25a=9*100 |